Analisis IFE, EFE, dan Balance Scorecard pada Grup Perusahaan PT Kirana Megatara - Christian Chandra Kusuma; Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
This research objective is aimed to analyze and evaluate the internal and external factors of the company and to design the balance scorecard as an alternative of performance measurement tools to support the company’s vision, mission, and strategy to achieve competitive advantage. The internal and external factors are to knowing what are the strengths and weaknesses of the company, also the opportunities and threats from the outside of the company. Based on the SWOT analysis, PT Kirana Megatara can identify the key success factors to compete with other companies in the same industry. Balanced Scorecard enables companies to record financial performance results as well as monitor progress in building the company's ability and to obtain intangible assets that required for future growth. Balance scorecard measures the performance of companies on the four perspectives of balanced: financial, customer, internal business processes, and learning growth to create strategy maps of the company. Based on the balance scorecard analysis, the current performance in PT Kirana Megatara is more focusing on financial perspective, which are growth of the sales and profitability increment. To achieve long term objective, PT Kirana Megatara should also concern of the other three perspectives of balance scorecard.